Improvıng Understandıng Of KPK And FPB Wıth Project Based Learnıng Model In Elementary School - Saiful Muslimin Muslimin; Minsih (Jurnal Elementaria Edukasia, 2024)
In developing the ability to count and solve formulas, learning mathematics in elementary schools also aims to advance the overall intellectual growth of students. The purpose of this article is to support educators in helping children comprehend mathematics lessons in KPK and FPB materials. in primary schools by using the Project Based Learning learning paradigm. The learning strategy that the instructor uses to convey the subject has a direct bearing on how well the students comprehend the KPK and FPB content. This study used quasi-experiments as part of its experimental design. A pretest and posttest description question is the tool utilized. 29 fourth-grade kids (N) from State Elementary School 2 Selo Boyolali served as the research subjects. The T test method was combined with the homogeneity test method and the data normalcy test for data analysis. The findings demonstrated how using the Project Based Learning methodology to teach KPK and FPB might enhance students' comprehension skills. substantiated by the experimental research 1 end findings, which had an average score of 73, 379. In contrast, with the same number of students—29—in experiment 2, the average student scored 80, 965. The T test findings showed that the project-based learning paradigm at State Elementary School 2 Selo Boyolali is improving the understanding of KPK and FPB pupils, with sig 0, 000 <0, 05 and the statements H₀ rejected and Hₐ accepted.